2022
DOI: 10.1002/batt.202100341
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancies of Commercial V2O5 Induced by Mechanical Force to Enhance the Diffusion of Zinc Ions in Aqueous Zinc Battery

Abstract: Rechargeable aqueous batteries with Zn 2 + as a media-ion are promising candidates for large-scale energy storage because of their intrinsic safety, low-cost and high energy-intensity. Vanadium based cathodic materials have gained significant attention in aqueous zinc-ion batteries (AZIBs) due to their high capacity and satisfactory cycle stability. However, more facile and efficient fabrication methods should be explored when considering future realistic application. Herein, commercial V 2 O 5 cathodes with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Interestingly, the activation barrier is reduced by 0.10 eV in the presence of O(1) vacancies but increases when the other two types of oxygen vacancies are present, indicating that the O(1) vacancies make it easier for Zn 2+ -ions to diffuse while the O(2) and O(3) vacancies make it more difficult. Because of this O(1) pathway, we may conclude that the O v present in V 2 O 5 effectively promote Zn 2+ -ion migration. ,, We also simulated Zn-ion migration along the [010] path when O(1) vacancies are present. As shown in Figure b, the activation energy for Zn-ion migration in pristine V 2 O 5 is 1.71 eV but decreases sharply to 0.63 eV when O(1) vacancies are present.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the activation barrier is reduced by 0.10 eV in the presence of O(1) vacancies but increases when the other two types of oxygen vacancies are present, indicating that the O(1) vacancies make it easier for Zn 2+ -ions to diffuse while the O(2) and O(3) vacancies make it more difficult. Because of this O(1) pathway, we may conclude that the O v present in V 2 O 5 effectively promote Zn 2+ -ion migration. ,, We also simulated Zn-ion migration along the [010] path when O(1) vacancies are present. As shown in Figure b, the activation energy for Zn-ion migration in pristine V 2 O 5 is 1.71 eV but decreases sharply to 0.63 eV when O(1) vacancies are present.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, vanadium-based oxides have captured con-siderable attention for ZIB cathodes benefiting from their rich valences and superior theoretical capacity. [20][21][22][23][24][25][26] For example, Yang et al reported that VO 2 (B) nanofibers with tunnel-like frameworks displayed a reversible capacity (357 mA h g −1 at 0.25 C upon 50 cycles). 7 Cheng et al reported that porous V 2 O 5 nanofibers exhibited a sustainable capacity (166 mA h g −1 at 2 C upon 500 cycles).…”
Section: Introductionmentioning
confidence: 99%
“…This mainly results from low electronic conductivity, electrochemical inertia, dissolution of vanadium element, volume change during cycling, and sluggish zinc-ion diffusion dynamics . Taking an example of commercial V 2 O 5 , the rate performance of this cathode for AZIBs can only achieve a capacity of 105 mAh g –1 at 2 A g –1 …”
Section: Introductionmentioning
confidence: 99%
“…20 Taking an example of commercial V 2 O 5 , the rate performance of this cathode for AZIBs can only achieve a capacity of 105 mAh g −1 at 2 A g −1 . 21 Recently, there are several strategies to tackle the abovementioned issues: (1) ion preinsertion (for example, H 2 O, 22 K + , 23 Co 2+ , 24 Zn 2+ , 3 NH 4 + , 25 Ca 2+ , 26 Na + , 27 ) acting as "pillars" to expand the interlayer spacing; (2) incorporation of heteroatom doping (S, N, etc.) into the inner structure to enhance the electronic conductivity; 28 and (3) structure engineering of V-based compounds by integrating some carbonaceous materials (graphene, 29,30 carbon nanotubes, 31,32 etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation